THE DIVERSITY AND DISTRIBUTION OF SEAGRASS IN KARANG TIRTA BEACH PADANG CITY, WEST SUMATERA - ARIEF A. PURNAMA; INDRA J. ZAKARIA; JABANG NURDIN (Syiah Kuala University, 2014)
Diversity and Distribution of Seagrass in Karang Tirta Beach Padang City, West Sumatera was conducted from April to June 2011. This study was intended to analyze the diversity, distribution pattern, coverage, composition and structure community of seagrass in Karang Tirta beach. Measurement of distribution aspect was analyzed with line transect method and sample of seagrass collected by using squares plot 0.5 x 0.5 m. Approximately 12 ha total of seagrass was estimated in various areas, such as: intertidal zone of tourism area, people settlement and mangrove zone. Seagrass distribution pattern was grouping category, and it was found 2 of 13 Species from Family Hidrocharitaceae of Indonesian seagrass exist, they were Thalassia hemprichii about 1.59 and Enhalus acoroides about 9.95. They were included into poor seagrass category with coverage ranged between 21.11% for T. hemprichii and 5.66% for E. acoroides. The highest species density was T. hemprichii (309.2 ind/m2) with appearance frequency value 100% and important value 252. The lowest species density was E. acoroides (7.73 ind/m2) with appearance frequency value 33.33% and important value 48.